The Positive Impact of Collaborative Learning for Student with Intellectual Disability in Inclusive School - Nadya Muniroh; Mita Apriyanti; Siti Musayaroh; Syari Yuliana (Department of Special Education, 2017)
Collaborative learning in inclusive classroom is one of indicators to measure the succes of the implementation of inclusive education. The collaboration betwen regular student and student with intellectual disability (ID) in learning can contribute positive impact on the development of student with ID. The study aim to analyze the eminence of colaborative learning for student with ID in inclusive school. The method employed in this study is descriptive quantitative. The 30 regular students as the samples of this study were determined through simple random probability sampling. The primary data is collected via questionnaires and were accomplished with observation and unstructured interviews for secondary data. The data were analyzed by descriptive analitic. The result revealed that collaborative learning is enabled to build student characterics such as: caring, empathy, and social sensitivity. Collaborative learning can decrease in labbeling and bullying toward the existence of student with ID.